2012
DOI: 10.1111/ajo.12015
|View full text |Cite
|
Sign up to set email alerts
|

What is the risk for parametrial involvement in women with early‐stage cervical cancer with tumour <20 mm and with negative sentinel lymph nodes?

Abstract: Aims: To evaluate the incidence of parametrial involvement in women with early-stage cervical cancer with tumour <20 mm and with negative sentinel lymph nodes (SLN). Methods: We reviewed the cases of all women who underwent radical hysterectomy and pelvic lymphadenectomy with SLN biopsy for invasive cervical cancer between April 2004 and December 2009. Parametrial involvement was defined as direct extension, nodal disease or spread through vascular channels. Results: From the 204 women who underwent radical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…Likewise, Klat et al, reported 204 patients who underwent radical surgery with SLN biopsy. They found no subjects with parametrial involvement among women with early-stage cervical cancer, with tumor < 20 mm in diameter and negative sentinel lymph nodes [17]. Our findings are consistent with those of Covens et al, who also detected a correlation between tumor size, LVSI, greater depth of invasion, and positive pelvic lymph nodes with parametrial involvement.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, Klat et al, reported 204 patients who underwent radical surgery with SLN biopsy. They found no subjects with parametrial involvement among women with early-stage cervical cancer, with tumor < 20 mm in diameter and negative sentinel lymph nodes [17]. Our findings are consistent with those of Covens et al, who also detected a correlation between tumor size, LVSI, greater depth of invasion, and positive pelvic lymph nodes with parametrial involvement.…”
Section: Discussionsupporting
confidence: 92%
“…They also found that the obturator lymph nodal group was generally the first and the most common site of tumor metastasis. Several authors have included negative pelvic lymph nodes as an inclusion criterion for a low-risk subgroup [4,5,7,11,26,27]. Assessment of this as a risk factor, of course, requires knowing the pelvic lymph node status, and sentinel lymph node (SLN) biopsy has been extensively described for the assessment of the pelvic lymph nodes in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, accurate SLN analysis requires coordinated efforts by a multidisciplinary team [6]. Less radical surgery in SLN-negative patients with small tumor volume is still experimental [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Strnad et al and Klat et al separately showed that patients with negative sentinel nodes do not have pathological parametrial involvement. 99,100 Although the pooled sensitivity of sentinel node mapping in fertility-sparing surgery was high, readers should be very cautious when interpreting the results. The number of studies are limited in this regard and the accuracy of frozen section is highly debated in cervical cancer sentinel node biopsies.…”
Section: Surgical Methodsmentioning
confidence: 99%